PENGARUH KETERAMPILAN DASAR MENGAJAR GURU TERHADAP MOTIVASI BELAJAR PESERTA DIDIK DI SEKOLAH DASAR - zahro, Fatimatuz; Alif Luthvi Azizah; Roy Kembar Habibi; Mujiyati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The issue of this research was the suboptimal learning motivation from the students at SD Negeri 8 Metro Timur, which hasn't met the minimum standards. This research aimed to examine the impact of teachers' basic teaching skills on students' learning motivation. The type of this research was quantitative with the combination of ex-post facto methods. The population of all the students of grade five at SD Negeri 8 Metro Timur consists of 48 students. The sampling technique was saturated sampling, so the sample in this study consisted of 48 students. Data came from a 35-item questionnaire, analyzed with the Regression test. The results indicated that teachers' basic teaching skills positively affect student motivation by 9.5% (based on R Square value of 0.095), in conclusion, there was an influence between teachers' basic teaching skills and student learning motivation, while others are influenced by other supporting factors.